Penerapan Model Think Pair and Share Untuk Meningkatkan Hasil Belajar Ekonomi Pada Siswa Kelas X SMA Negeri 5 Halmahera Utara - Cornelis Saliha (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research was conducted based on the results of observations carried out in class X SMA Negeri Halmahera Utara where it was found that in the implementation of learning the teacher used his role as the holder of learning control too much, so that the teacher always dominated all learning activities. When teaching and learning activities take place, the teacher does not create active communication between students and teachers, students only listen to the information provided by the teacher and are not given the opportunity to discover and develop their own knowledge. Some students just play in class and others just talk to their friends, so learning Economics tends to be boring. So that student learning outcomes are not satisfactory, only 4 students get high scores, 8 other students get low scores. This study aims to improve learning outcomes in Economics through the Think Pair and Share model of class X students of SMA Negeri Halmahera Utara. The method used in this research is to take a Classroom Action Research (CAR) design with the stages of planning, action, observation, and reflection and is carried out in two cycles. In the implementation of the first cycle student learning outcomes 56.6% but in the second cycle increased to 88.3%. From the results of this study, the following conclusions were drawn: The application of the Think Pair and Share model can improve the economics learning outcomes of class X SMA Negeri Halmahera Utara. It is expected that class X teachers can use the Think Pair and Share learning model in Economics, and students are more enthusiastic in teaching and learning activities.